Contribution A La Connaissance Hydrogéologique Et Hydrogéochimique Des Aquifères De La Région De Beni-Hassan (Rif Septentrional, Maroc) - Alilouch, Redouan; Morabiti, Karim El; Mrihi, Abdelaziz El (European Scientific Journal, ESJ, 2017)
The contribution to the hydrogeological, hydrochimical and bacteriological knowledge of the aquifers of Beni Hassan (Northern Rif) area constitutes one of the main aims of this study. This work aims: i) to make the inventory of water supply points of the area, ii) to study their relationship with the detrital and carbonated formations, as well as with the neighbouring some ones and iii) Clear the quality and the characteristics of the Chemical water type of these aquifers. The study area is located in the north of Morocco, in the septentrional Rif between the following lambert coordinates (XMin= 501000m and XMax= 507000m) and (YMin= 523000m and YMax= 527000m). This latter belongs to the flyschs nappes (Mauritanian and massylien Flysch), the internal domain (Calcareous Dorsal) and external domain (Tanger Unit). The zone is characterized by two watersheds ( â€˜â€˜Wadiâ€™â€™ watersheds Moulay Bouchta and â€œWadiâ€ watershed Martil), which is characterized in turn by aquifers of different lithological nature.